A giant aggressive angiomyxoma of vulva in a young woman: A case report. Issue 2 (January 2019) - Xie, Yao; Qian, Yanping; Zou, Bingyu
Abstract: Rationale: Aggressive angiomyxoma (AAM) is a rare and benign invasive mesenchymal stromal tumor predominantly in women at reproductive age. AAM tends to relapse locally and should be differentially diagnosed from other mesenchymal tumors. Patient concerns: We report here a rare case of massive vulvar AAM in a 22-year-old Chinese woman with left labia majora mass with ulcer. Diagnoses: The diagnosis "aggressive angiomyxoma of vulva" was based on clinicopathologic and immunohistochemical features. Interventions: A surgery with local excision of the mass was performed. Outcomes: The patient was discharged 12 days after the surgery. There was no AAM recurrence or metastasis in a period of 12-month follow-up. Lessons: The vulvar AAM is a benign and aggressive mesenchymal tumor. In this case, we present the diagnosis, treatment, and prognosis for vulvar AAM. The tumor was removed completely by the surgery, but a long-term follow-up is requisite for surveilling on recurrence.